Estudio de parasitismo de cría del Renegrido (Molothrus bonariensis) en Calandria (Mimus saturninus), en Villa María, Córdoba - Salvador, Sergio A. (1984)
The host-parasite interactions between Chalk-browed Mockingbirds ( Mimus saturninus ) and Shiny Cowbirds ( Molothrus bonariensis ) were studied around Villa María, Córdoba, Argentina, between 1979 -1984. The incidence of parasitism was 81/92 or 88,04%. Mockingbirds in the study site accepted Cowbird eggs, even those of the immaculate morph, which are rejected in Buenos Aires. Incubation period for the host was 14-15 days, for the parasite 12-13 days, with nestling periods of 13 -14 and 14 -15 days respectively. Breeding season of host and parasite overlapped almost completety. In a better studied subsample of parasitized nests success for the host was 7,70% (ratio Fledglings//eggs of 3/39) and for the parasite 6,45% (2/31). Cowbirds punctured and removed host eggs. Mockingbirds were probably the best local hosts for the Cowbirds.